Guía para la aplicación de audio branding apoyado en el neuromarketing, como elemento proyectivo para reforzar la identidad de marca. Caso: cerámicas Rialto - Malo Corral, José Miguel (2014)
In a world where every day the products are more alike, the advantage comes from the experience that they provide to the consumer. At the end, a brand is the sum of a promise and an experience. For the construction and reinforcement of these you can use the five senses that human beings have, it is best to combine them all and create unforgettable experiences. The subject relies specifically on the sense of hearing, and how it can influence positively to reinforce brand identities. Living in a society where visual communication is so strong, stimulus competition is so great that companies are looking for ways to retain the attention of consumers. Brands need new elements to be easily recognized and one of the ways to achieve that is through melodies and sound compositions. And the interesting thing is that this can be applied in different media such as television, the internet and points of sale, where brands have direct contact with the consumer. In general the trend continues to generate experiences for greater proximity to the audience, and make it feel part of the brands. Like anything that has to do with senses, the sense of hearing is extremely important, as it has a fairly high degree of recall, so should be given special attention and care. This will allow consumers to identify and feel identified with certain products by only listening to a short melody ora pair of musical notes.